Cryopreservation of secondary Protocorms, an alternative pathway for conservation of Western Australian terrestrial orchids - Bustam, B.; Dixon, Kingsley; Bunn, E. (International Society for Horticultural Science, 2015)
Orchidaceae contains many species worldwide with a high extinction risk. Efforts to overcome this problem include ex situ approaches such as seed banking and in vitro germination of orchid seed symbiotically or asymbiotically. The rationale behind this study was to investigate alternative protocols for orchid propagation that would reduce dependence on valuable seed stocks especially with rare and endangered orchid species, while still enabling experiments to be conducted to improve in vitro and long-term storage methods. We report on research into secondary protocorm proliferation and cryopreservation of native orchid species conducted at Kings Park Botanic Garden (KPBG), Perth, Western Australia. Secondary protocorms of Caladenia latifolia R.Br. were produced from primary protocorms following asymbiotic germination using a protocol developed at Kings Park. A cryostorage protocol developed for the primary protocorms was utilized and modified for secondary protocorms. This was based on droplet vitrification and storage in Liquid Nitrogen (LN). Secondary protocorms of C. latifolia were precultured on a =MS with 0.2 M raffinose solid medium for 2 days, followed by PVS2 treatment for 20 minutes at 0°C, then protocorms were placed on foil strips in droplets of PVS2 and stored in LN. Control protocorms were taken from PVS2 treated with washing solution (1 M sucrose) and placed on recovery medium without LN storage. All secondary protocorms survived cryopreservation without browning and proceeded to develop into plantlets. However regeneration to plantlets took up to 20 weeks with C. latifolia, and further experiments will be necessary to shorten the regeneration time if possible. However the results are promising and will be trialled with other orchids, including rare species.